Level of Acceptability of Sweet Squash Jam (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Spain brought its tradition of making jams to the West Indies. Marmalade came into existence in the 16th century when Mary Queen of Scots’ physician mixed orange and sugar to help with her seasickness. Thus, marmalade became a favorite of royalty. Although the immigrants to the US brought their recipes with them, the first book on making jam appeared in this country in the 17th century. Early settlers in New England used other ways of making jam, such as using molasses, honey, and maple sugar to give it a sweet taste. Squash is also known as summer squash. Yellow varieties of squash provide numerous health benefits, such as vitamins A, vitamin B6, vitamin C, folate, magnesium, fiber, riboflavin, phosphorus, and potassium. The reason why we made this product was to make our society healthy because by providing a healthy snack option instead of eating junk food. Here, an experimental method was used. The researchers used random sampling to select the respondents. The researchers chose 60 Grade 12 Home Economics (HE) Strand students and 10 HE teachers as respondents. The results showed that the differences in the assessments of students and teachers in terms of taste, aroma, nutritional value, and presentation were not significant because of the same results for the two groups of respondents, which had the verbal interpretation of strongly agree for students and very strongly agree for teachers. Sweet squash jam is the best food because of its nutrients. The respondents said that the product has unique taste and concept because researchers replaced fruits with vegetables. The researchers recommended that future researchers should also make sweet squash jam as their innovative product to study it further. The researchers recommended that future researchers can make sweet banana Jam if the product is out of stock.
Keywords: experimental, theoretical framework, sampling techniques